Effect of Transition Metals Oxides on the Physical and Mechanical Properties of Sintered Tungsten Heavy Alloys - Ayman H. Elsayed; Mohamed A. Sayed; Osama M. Dawood; Walid M. Daoush (Crystals, 2020)
The addition of transition element oxides to tungsten heavy alloys (WHAs) fabricated by powder metallurgy technique provides new materials with higher density and electrical conductivity, which may be adequate in some applications such as kinetic energy penetrators. Additionally, materials with higher electrical conductivity are required for electrical contact applications such as electrical discharge machining (EDM) electrode materials. WHAs were fabricated by compacting its mixed constituents followed by sintering. Ni, Co and Fe are used as binding phases of the tungsten particles and oxides of Zr, Ti and Y are used as oxide dispersing strengthening (ODS) agents of the sintered materials. The results show that all of the chosen factors (i.e., pressure of compaction process, temperature of sintering, type of binding material and type of oxide) have clear effects on all properties of ODS tungsten heavy alloy specimens. The density and electrical conductivity increase with the increase in sintering temperature. Hardness and compression strength were also measured to evaluate the mechanical properties of sintered samples.